2017
DOI: 10.12681/eh.11514
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear models for describing development and fecundity of the pseudococcid predators Nephus includens and Nephus bisignatus

Abstract: Among several mathematical models used to describe the development or the fecundity of insects the equations of Enkegaard, Analytis, Bieri 1 and Bieri 2 could describe both biological features. In the current study these equations used to describe the development and fecundity of two pseudococcid predators [Nephus includens (Kirsch) ranged 0.8246-0.9704, 9.2729-24.0736 and (-246.82) -(-115.34) respectively]. Conclusively, from the tested models the Bieri-1 equation was proved as the most appropriate for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Tranfaglia and Viggiani (1972) found that the female laid 150.6 eggs and lived 74 days at 25-27°C preying on P. citri. Kontodimas (2003Kontodimas ( , 2004 studied the effect of temperature on many biological features of N. includens. The aver age total fecundity was 49.…”
Section: Nephusmentioning
confidence: 99%
“…Tranfaglia and Viggiani (1972) found that the female laid 150.6 eggs and lived 74 days at 25-27°C preying on P. citri. Kontodimas (2003Kontodimas ( , 2004 studied the effect of temperature on many biological features of N. includens. The aver age total fecundity was 49.…”
Section: Nephusmentioning
confidence: 99%
“…Several non-linear models have been developed to describe the relationship between temperature and the developmental rate and/or fecundity of insects and mites [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Some of these models can be used for both developmental data and fecundity [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several non-linear models have been developed to describe the relationship between temperature and the developmental rate and/or fecundity of insects and mites [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Some of these models can be used for both developmental data and fecundity [ 41 ]. Among these, we selected the following four non-linear models to describe the relationship between temperature and age-dependent fecundity of S. gilvifrons .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest model is a linear one which enables the prediction of the lower developmental threshold and thermal constant within limited ranges of temperatures (Campbell et al, 1974;Kontodimas et al, 2004;Shi et al, 2011;Brar et al, 2015). Nevertheless, for a more accurate description of the temperature dependence of mean developmental rates over a wide range of temperatures, there are several nonlinear models that enable us to estimate the optimum temperature for development and upper developmental threshold (Logan et al, 1974;Lactin et al, 1995;Brière et al, 1998;Kontodimas et al, 2004, Kontodimas, 2012.…”
Section: Lower Developmental Thresholdmentioning
confidence: 99%